2012
DOI: 10.1038/pj.2012.123
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the mean size of polyphenyleneoxide microvoids, as studied by Xe sorption and 129Xe NMR chemical shift analyses

Abstract: Both the Xe sorption isotherms and 129 Xe NMR spectra of poly(2,6-dimethyl-1,4-phenylene oxide), PPO, were obtained across a temperature range of -55 1C to þ 80 1C to investigate the temperature dependence of the gas sorption and the unrelaxed volume of PPO. All of the obtained sorption isotherms were analyzed based on the dual-mode sorption model, and the Langmuir saturation constant, C H 0 , which corresponds to the unrelaxed volume, was determined by curve fitting. The values of C H 0 increased linearly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A commonly used method to determine T g for a polymer is to calculate its density as a function of temperature, that is, to obtain the ρ(T) curve. [15,[39][40][41][42][43] One example is shown in Figure 2 for ULTEM (i.e., 4,4'BPADA + MPD). The value of T g can be determined from the intersection of the two linear fits to ρ(T), one for the lower and the other for the higher temperature region.…”
Section: All-atom MD Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A commonly used method to determine T g for a polymer is to calculate its density as a function of temperature, that is, to obtain the ρ(T) curve. [15,[39][40][41][42][43] One example is shown in Figure 2 for ULTEM (i.e., 4,4'BPADA + MPD). The value of T g can be determined from the intersection of the two linear fits to ρ(T), one for the lower and the other for the higher temperature region.…”
Section: All-atom MD Simulation Methodsmentioning
confidence: 99%
“…A commonly used protocol to determine T g for a polymer is to calculate its density as a function of temperature, i.e., to obtain the ρ(T ) curve. [35][36][37][38][39][40] One example is shown in Fig. 2 for ULTEM (i.e., 4,4'BPADA+MPD).…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al studied several other glassy polymeric systems, including poly(2,6dimethyl-1,4-phenylene oxide) (PPO) [88], PPO/PS blends [89], and tetramethyl bisphenol A polycarbonate (TMPC)/PS blends [90], using 129 Xe NMR and Xe sorption measurements. For these studies, the sorption behavior of xenon in glassy polymers was described using a dual-mode adsorption model.…”
Section: Polymersmentioning
confidence: 99%
“…Most recently, we have reported the Xe sorption properties and 129 Xe NMR spectra of PPO measured at various temperatures. 10 By analyzing the 129 Xe NMR chemical shift, it was observed that the mean diameter of the microvoids in PPO increases linearly with decreasing temperature, and the extrapolated value at the glasstransition temperature was close to 4.4 Å , which is the diameter of a Xe atom. Furthermore, the characteristic cavity in a crystalline region of poly(4-methyl-1-pentene) (PMP) was investigated using gas permeation and 129 Xe NMR measurements of PMP membranes with various degrees of crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] As the Xe atom has a very large polarizability, the 129 Xe NMR signal is sensitive and easily influenced by its environment; specifically, the induced 129 Xe NMR chemical shift is strongly altered by the Xe electron density. The NMR chemical shifts for glassy polymers exhibited a nonlinear low-field shift with an increasing amount of Xe sorption because of the fast exchange of Xe between the Henry and Langmuir sites; therefore, we calculated the NMR chemical shifts for each site using the dual-mode sorption parameters.…”
Section: Introductionmentioning
confidence: 99%